Preliminary study on magnetic tracking-based planar shape sensing and navigation for flexible surgical robots in transoral surgery: methods and phantom experiments - Song, Shuang; Zhang, Changchun; Liu, Li; Meng, Max Q.-H. (International journal for computer assisted radiology and surgery, 2018)
Purpose Flexible surgical robot can work in confined and complex environments, which makes it a good option for minimally invasive surgery. In order to utilize flexible manipulators in complicated and constrained surgical environments, it is of great significance to monitor the position and shape of the curvilinear manipulator in real time during the procedures. In this paper, we propose a magnetic tracking-based planar shape sensing and navigation system for flexible surgical robots in the transoral surgery. The system can provide the real-time tip position and shape information of the robot during the operation. Methods We use wire-driven flexible robot to serve as the manipulator. It has three degrees of freedom. A permanent magnet is mounted at the distal end of the robot. Its magnetic field can be sensed with a magnetic sensor array. Therefore, position and orientation of the tip can be estimated utilizing a tracking method. A shape sensing algorithm is then carried out to estimate the real-time shape based on the tip pose. With the tip pose and shape display in the 3D reconstructed CT model, navigation can be achieved. Results Using the proposed system, we carried out planar navigation experiments on a skull phantom to touch three different target positions under the navigation of the skull display interface. During the experiments, the real-time shape has been well monitored and distance errors between the robot tip and the targets in the skull have been recorded. The mean navigation error is 2.07 ± 0.71 mm, while the maximum error is 3.2 mm. Conclusion The proposed method provides the advantages that no sensors are needed to mount on the robot and no line-of-sight problem. Experimental results verified the feasibility of the proposed method.